HEART HEALTH EDUCATION AND SCREENING IN ELDERLY AT POSBINDU BENCONGAN INDAH TANGERANG - Gultom, Eva Chris Veronica; Manurung, Evanny Indah; Arkianti, Maria Maxmila Yoche; Saputra, Bima Adi; Sihombing, Riama Marlyn; Tahapary , Prisca A.; Silalahi, Elfrida (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2025)
Introduction: Hipertention is one of the risk factors of cardiovascular disease in elderly. The purpose of this activity is to provide education about hypertension and conduct health screening which includes height, blood pressure, weight, abdominal circumference, GDS, total cholesterol, and uric acid. Methods: The activity was carried out on March 2023 by conducting health checks, namely measuring blood pressure, height, weight, abdominal circumference, and blood sugar, cholesterol, and uric acid, as well as providing education about hypertension to 52 residents, at the Posbindu RW 05 Bencongan community hall. The level of knowledge of the participants was assessed based on the contents of the test sheet given at the time before and after  intervention. The topic of hypertension is given as it is one of the major contributing factors to cardiovascular disease. While total cholesterol and uric acid are other risk factors that cause these diseases. Results: Participants consisted of 36.5% men, 63.5% women, with the elderly category 48.1% and pre-elderly 38.4%. The results of the IMT examination were fat category 54%, male abdominal circumference (normal) 12.8%, female abdominal circumference (normal) 48.9%, hypertension 65.38%, normal blood sugar 96.07%, high total cholesterol 30.8%, male uric acid (high) 50%, female uric acid (high) 50%. Meanwhile, the participants' pre-test results averaged 52.5%, and post-test 74.1%. Conclusion:  The increase in participants' knowledge about hypertension and the increase in the value of some measurement results are expected that participants can adjust their lifestyle and diet to avoid the occurrence of cardiovascular disease.